Physicochemical and Organoleptic Characteristics of Fruit Leather Made from Kecombrang (Etlingera elatior) and Soursop (Annona muricata Linn) Juice with the Addition of Hydrocolloids - Rachmawati Nurma Fatikhah Nur; Ulya Sarofa; Hadi Munarko (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Fruit leather is a semi-moist, fruit-based food product in the form of thin, rollable sheets, produced through the drying of fruit pulp or juice. The use of kecombrang and soursop fruits with the addition of hydrocolloids is expected to enhance the functional value while improving the texture of fruit leather. This study aims to determine the effect of the proportions of kecombrang and soursop juices with the addition of hydrocolloids on the physicochemical and organoleptic characteristics of fruit leather. This study used a two factor Complete Randomized Design (CRD) with two replicates. Factor I was the ratio of kecombrang and soursop juices (70:30, 60:40, and 50:50), while Factor II was the addition of hydrocolloids (1% CMC, 0.3% ?-carrageenan, and 1.5% gum arabic). The results of this study show that the proportions of kecombrang and soursop juices with the addition of hydrocolloids, affect the physicochemical characteristics of fruit leather. The best treatment analysis was conducted by assigning the highest weight to tensile strength and the highest level of panelist acceptance of the fruit leather’s texture. The best treatment was obtained with a 60:40 ratio of kecombrang and soursop juice with the addition of 1% CMC (Carboxymethyl Cellulose). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production